Euglycaemic diabetic ketoacidosis in a patient with type 2 diabetes started on empagliflozin. (13th May 2016) - Rashid, Owais; Farooq, Saad; Kiran, Zareen; Islam, Najmul
Abstract : Diabetes ketoacidosis (DKA) is largely associated with type 1 diabetes and has hyperglycaemia as a cardinal feature. We discuss the case of a 42-year-old man, a patient with type 2 diabetes, who presented to the emergency room, with nausea, vomiting and abdominal pain. He had recently changed his diabetes medications and started on an SGLT2 inhibitor (empagliflozin) along with metformin, pioglitazone, liraglutide and self-adjusted exogenous insulin. DKA was suspected in the wake of clinical examination and lab findings but glucose levels were below the cut-off for DKA; therefore, he was diagnosed with euglycaemic DKA. He was successfully managed with intravenous hydration and insulin infusion. We discuss the link of SGLT2 inhibitors with DKA and the pathophysiology behind euglycaemic DKA.